2009
DOI: 10.1111/j.1365-2516.2008.01651.x
|View full text |Cite
|
Sign up to set email alerts
|

Ankle arthropathy in the haemophilic patient: a description of a novel ankle arthrodesis technique

Abstract: The ankle joint is well known to show early involvement in severe haemophilia. We describe a novel operative technique developed by the senior author. This combines a medial approach to the ankle, medial malleolar osteotomy, bone graft and compression with staples. All patients had excellent pain relief and improvement in function with 100% achieving bony union. There was a significant improvement in Mazur ankle scores following ankle fusion (P < 0.01). This surgical technique gives good results which are repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
0
10
0
2
Order By: Relevance
“…Mann et al . , described the results of eight ankle fusions with a mean follow‐up of nearly 4 years. The authors reported excellent pain relief and improvements in function, with one patient requiring screw removal due to pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mann et al . , described the results of eight ankle fusions with a mean follow‐up of nearly 4 years. The authors reported excellent pain relief and improvements in function, with one patient requiring screw removal due to pain.…”
Section: Discussionmentioning
confidence: 99%
“…While ankle fusion has long been accepted as the procedure of choice for end‐stage arthropathy in the haemophilic patient, there is a paucity of studies evaluating its long‐term outcome. Most available studies have small sample sizes with short follow‐up times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodriguez-Merchan [27] reported about good short-term results in two patients underwent tibiotalar fusion. Only recently Mann et al [31] described a novel ankle arthrodesis technique using medial approach to the ankle, bone graft and compression with staples. This technique was used in seven patients with haemophilia A and in one patient with haemophilia B, all patients were satisfied at the latest follow-up of 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, VWD is a known reason for haemophilic arthropathy. ankle arthrodesis, TAR) [15,29,[55][56][57][58][59][60][61][62][63]. Sood et al [8] described similarity in joint function limitations in patients with Type 3 VWD and moderate haemophilia A.…”
Section: Discussionmentioning
confidence: 99%